Macropinocytosis Exploitation by Cancers and Cancer Therapeutics - Ha, Kevin D.; Bidlingmaier, Scott M.; Liu, Bin (Frontiers in Physiology, 2016)
Macropinocytosis has long been known as a primary method for cellular intake of fluid-phase and membrane-bound bulk cargo. This review seeks to re-examine the latest studies to emphasize how cancers exploit macropinocytosis to further their tumorigenesis, including details in how macropinocytosis can be adapted to serve diverse functions. Furthermore, this review will also cover the latest endeavors in targeting macropinocytosis as an avenue for novel therapeutics.